Effect of learning centered on emotional management on the appreciation towards mathematics in university students - Vidaurre García, Wilmer Enrique; Santisteban Salazar, Mirtha Yvis; Santisteban Salazar, Nelson César (International Journal of Evaluation and Research in Education (IJERE), 2025)
Emotions are related to the motivation to learn, being necessary the development of courses designed to improve the appreciation for mathematics. The study determined the effect of a learning program focused on the management of emotions on the appreciation of mathematics in students of a private university in northeastern Peru. A quasi-experimental design study was planned in which 108 students of the first cycle of psychology, initial and elementary education careers who were taking the subject of logical thinking during the first academic semester of 2019 participated. Data were collected through a pre- and post-intervention survey, using a questionnaire consisting of 39 items evaluated by experts and with a Cronbach’s coefficient of 0.95 and were analyzed using descriptive statistics and paired samples t-test. The program consisted of 15 learning sessions that included pedagogical strategies to activate students’ thoughts of interest in mathematics. After the application of the program, the level of appreciation in each of the groups increased significantly from pretest to posttest (p<0.000). The intervention positively influenced students’ appreciation in mathematics. Thus, emotional management can be an effective strategy to improve attitudes in higher education, and this approach can be replicated in other educational levels and disciplines.